A STUDY ON AWARENESS OF VARIOUS LOAN SCHEMES PROVIDED BY THE FINANCIAL INSTITUTIONS AND ITS IMPACT ON FINANCIAL INCLUSION OF BANJARA COMMUNITY - Rathod, Yogesh Ramchandra; Shetiya, Mahavir Manikchand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Financial inclusion is essential for economic development, especially for marginalized communities like the Banjara community in India. This study aims to investigate the awareness of various loan schemes provided by financial institutions and its impact on the financial inclusion of the Banjara community. A mixed-methods approach, including qualitative and quantitative methods, was used to gather data from Banjara community members. The study found that although there are several loan schemes available, the level of awareness among the Banjara community is relatively low. However, those who were aware of the schemes had benefitted from them and reported an improvement in their financial situation. The study recommends that financial institutions and policymakers should focus on increasing awareness of loan schemes to promote financial inclusion among marginalized communities like the Banjara community.